Gastrointestinal parasites in Asian and African elephants: a systematic review - Z., Qurratul-Saadah; Che-Amat, A.; Syed-Hussain, S.S.; Kamaludden, J.; Ariffin, S.M.Z.; Basripuzi, N.H.; A.A., Nor-Azlina (Malaysian Society for Parasitology, 2023)
Gastrointestinal parasites (GIPs) in elephants have been reported in several studies over the last decades. Nonetheless, comprehensive data on clinicopathology of elephant GIPs, parasite burden threshold value, and the effectiveness of conventional anthelmintic drugs are still lacking. Herein, we have systematically reviewed the available knowledge on elephant GIPs identified among different parts of the world based on their prevalence, epidemiology, pathology, diagnosis, treatment, and control. Two electronic databases were searched for publications that met the inclusion criteria. About19 English journal articles published between year of 2011- 2021 were included. The main GIPs reported in elephants were Cyathostomidae (at least 14 species), Ancylostomidae, Haemonchus contortus, Trichostrongylus colubriformis, Oesophagostomum columbianum, Oesophagostomum aceleatum, Ascarids, Trichurids, Strongyloides, Anophlocephalidae, flukes, and Coccidia across different parts of the world, including Malaysia, Indonesia, Thailand, Myanmar, Sri Lanka, India, Kenya, Nigeria, and South Africa. Most elephants show no clinical signs until the equilibrium between parasite and host is disturbed. The common diagnostic methods for GIPs are traditional direct smear, faecal floatation, sedimentation, and McMaster egg counting technique, all involving morphological identification. However, some articles described the use of molecular detection to characterise common GIPs of elephants. Although benzimidazoles and macrocyclic lactones group of anthelmintic are the most conventional GIPs treatment and control for captive and semi-captive elephants, there is limited data on the threshold value of faecal egg count as the baseline for treatment decision. Over the last decades, various studies regarding elephant GIPs have been conducted. However, more focused and systematic studies are required to enhance our knowledge in multiple aspects of elephant parasitology to find effective solutions and improve elephant health.